2005
DOI: 10.3233/jad-2004-6s614
|View full text |Cite
|
Sign up to set email alerts
|

Novel nitrates as NO mimetics directed at Alzheimer's disease

Abstract: GT 1061 is a novel therapeutic agent that is in Phase 1 clinical studies for Alzheimer's disease. GT 1061 is one of a family of novel nitrates that have demonstrated neuroprotective properties and cognition-and memory-enhancing properties in animal models. The prototype of this family, GT 715, has been reported effectively to dissociate the neuromodulatory and the systemic hypotensive effects of nitrates, the latter seriously limiting the therapeutic use of classical nitrates. Further data on the novel nitrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 85 publications
1
29
0
Order By: Relevance
“…These results are in agreement with the observation that NO-mimetic molecules may reverse the cognitive impairment caused by scopolamine (Thatcher et al, 2004), or by forebrain cholinergic depletion (Bennett et al, 2007), suggesting that stimulating the NO/cGMP signal transduction system can provide new, effective treatments for cognitive disorders. With regard to the beneficial effect on memory, it is interesting to note that inhibition of PDE5 activity during a time window starting immediately after training for fear learning or after acquisition of the spatial task and ending at no more than 4 h after them improves learning in the transgenic animals.…”
Section: Discussionsupporting
confidence: 81%
“…These results are in agreement with the observation that NO-mimetic molecules may reverse the cognitive impairment caused by scopolamine (Thatcher et al, 2004), or by forebrain cholinergic depletion (Bennett et al, 2007), suggesting that stimulating the NO/cGMP signal transduction system can provide new, effective treatments for cognitive disorders. With regard to the beneficial effect on memory, it is interesting to note that inhibition of PDE5 activity during a time window starting immediately after training for fear learning or after acquisition of the spatial task and ending at no more than 4 h after them improves learning in the transgenic animals.…”
Section: Discussionsupporting
confidence: 81%
“…In this model of neuronal injury [204] GT 715 was observed to significantly decrease the brain injury induced by the malonate neurotoxin at both the behavioural and neurochemical levels. Preservation of GABA levels in the striatum after malonate injection, measured as an index of the neuronal cell population, and a markedly decreased response to apomorphine in ipsolateral turning indicated that neuronal injury was significantly inhibited by GT 715 administration, and that normal function within the neostriatum was maintained [202]. These results reinforce our previous unpublished observations in a Parkinson's animal model and reported observations on the neuroprotective activity of GT 715 in the rat transient MCAO model of ischemic stroke wherein s.c. delivery of drug 2h or 4h after ischemia produced a significant reduction in infarct volume (58% reduction in total and 72%reduction in cortical infarct volumes at 4h) [190].…”
Section: Nitrates As No Mimetic Therapeutics In Admentioning
confidence: 99%
“…GT 715 supported the postulate that neuromodulatory and hypotensive effects of nitrates can be dissociated. Demonstration of the neuromodulatory effects of GT 715 was observed in a variety of models of neuroprotection: (a) in the middle cerebral artery occlusion (MCAO) rat model of focal ischemic stroke [201], (b) in the 6-hydroxydopamine-lesion rat model of Parkinson's Disease, and (c) in the malonate-lesion rat model of excitotoxic neurodegeneration [202].…”
Section: Nitrates As No Mimetic Therapeutics In Admentioning
confidence: 99%
See 1 more Smart Citation
“…Other than classical nitrates or hybrid nitrates, NO donor nonsteroidal anti-inflammatory drugs [123][124][125][126][127], an additional therapeutic approach is to block the degradation of cGMP by using PDE5 inhibitors (PDE5-Is). Over the past few years, our group and others have demonstrated that treatment with PDE5-Is rescues synaptic and memory deficits in the APP/ PS1 mouse model of AD, restoring phospho-CREB levels and decreasing Aβ load [112,128].…”
Section: The Erk1/2 Mitogen-activated Protein Kinase Pathwaymentioning
confidence: 99%